Impact of Globalization on Social Development and Culture of Primary School Students - Amri, Khairul; Sugiharto, Sugiharto; Ritonga, Maharani; Pane, Aina Ristanti (Jurnal Gentala Pendidikan Dasar, 2024)
This research examines the impact of globalization on the social and cultural development of students at UPT SPF SDN 101990 Bangun Purba. This research uses a qualitative approach with in-depth interview methods, participant observation, and documentation analysis. This research aims to describe the impact of globalization, identify cultural changes, analyze student adaptation, and provide recommendations for educators and policy makers. The research results show that globalization has had a positive impact in the form of increasing access to knowledge through technology, developing social skills, cultural enrichment, and increasing environmental and social awareness. Students demonstrate better communication skills,participation in collaborative activities, and a tolerant attitude towards cultural diversity. This research supports constructivism theory and intercultural contact theory, provides important insights for managing the influence of globalization in elementary schools, and becomes a reference for educational strategies that are responsive to globalization